Incorporating Local Market Conditions into Pop Mart's Market Entry Strategy for the Czech Republic - Zhang, Shijing; Machek, Ondřej, 1985-; Kubíček, Aleš; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This thesis explores a localized marketing strategy for POP MART’s expansion into the Czech market, focusing on identifying the most effective market entry method. Through a comprehensive analysis of the PEST model, the external market environment is analyzed, followed by a modified Porter's Five Forces analysis for the emerging toy industry. The evaluation of internal strategies, together with both opportunities and challenges through SWOT was conducted, followed by the Marketing Mix localized for the Czech market. A consumer survey was also conducted to analyze pricing preferences, offering key insights for developing a tailored pricing strategy, while cost estimation ensures financial feasibility. The thesis also evaluates potential entry strategies, including joint ventures and strategic alliances, to determine the optimal approach for market penetration. By leveraging its IP plus blind box marketing model, this research provides recommendations to help POP MART build a competitive and sustainable presence in the Czech Republic.
Vedoucí práce: Ondřej Machek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses